Surface and Interface Modification of Electrode Materials for Lithium-Ion Batteries With Organic Liquid Electrolyte - Guo, Weijia; Meng, Yating; Hu, Yi; Wu, Xuan; Ju, Zhicheng; Zhuang, Quanchao (Frontiers in Energy Research, 2020)
Developing efficient energy conversion and storage technology is gradually more and more necessary with the increasing shortage of fuel resources and the growingly serious environmental pollution. Demands and applications of the emerging technology such as new-energy vehicles and massive-scale energy storage are also further expanded. Therefore, new rechargeable batteries, especially the most promising electrochemical energy storage device-lithium ion batteries (LIBs), play an important role on the energy storage stage. LIBs have achieved large-scale industrialization, while the various nonnegligible problems still exist compared with the demand in the future. Significantly, most electrochemical reactions occur on the electrode-electrolyte interface, and interface components, surface structure and property determine the performance of batteries. Thus, numerous efforts have been made to form or modify the electrode-electrolyte interface. This article reviews recent researches about surface-interface modification in electrode and organic liquid electrolyte in LIBs. Specifically, the basic growth mechanism of electrolyte-electrode interface and SEI layer is referred. The summary and discussion of surface modification and the innovative design of SEI layer are mainly focused on. Finally, future research directions focusing on electrode-electrolyte interface for lithium storage are proposed.